The Effect of Land Fragmentation on Poverty Levels in Rwamucucu Sub-County Rukiga District. - Nasasira, Severina (Kabale University, 2024)
Land fragmentation has been a major concern worldwide and has spread as a result of various institutional, political, historical, and sociological factors such as inheritance laws, collectivization, and consolidation processes. Most societies in developed countries are characterized by a culture of land fragmentation that affects agricultural production. For instance, agricultural land in Europe was highly fragmented into land parcels due to inefficiency in distribution and allocating land use rights to households. The purpose of this study was to assess the effects of land fragmentation on poverty levels in the Rwamucucu sub-county Rukiga District.